Socioedemographic determinants of glycaemic control in young diabetic patients in peninsular Malaysia - Ismail, I.S.; Nazaimoon, W.M.W.; Mohamad, W.B.W.; Letchuman, R.; Singaraveloo, M.; Pendek, R.; Faridah, I.; Rasat, R.; Sheriff, I.H.; Khalid, B.A.K. (2000)
Recent studies have shown that good glycaemic control can prevent the development of diabetic complications in type 1 and type 2 diabetes. We wished to observe the glycaemic control in patients from different centres in Peninsular Malaysia and the factors that determine it. We recruited 926 patients with diabetes diagnosed before age 40 years from seven different centres, with proportionate representation from the three main ethnic groups. Clinical history and physical examination were done and blood taken for HbA(1c) and fasting glucose. The overall glycaemic control was poor with geometric mean HbA(1c) of 8.6 whilst 61.1 of the patients had HbA(1c) greater than 8. Glycaemic control in patients with type 2 diabetes varied between various centres and ethnic groups, with the best control obtained in Chinese patients. Significant predictors of HbA(1c) in both type 1 and type 2 diabetes include access to nurse educators, ethnic background and WHR. In type 2 diabetes, use of insulin was a significant predictor, while in type 1 diabetes, household income was a significant predictor. Socioeconomic status did not have a significant effect in type 2 diabetes. There were no significant differences in the glycaemic control in patients with different educational status. In conclusion, glycaemic control in big hospitals in Malaysia was poor, and was closely related to the availability of diabetes care facilities and ethnic group, rather than socioeconomic status. (C) 2000 Elsevier Science Ireland Ltd. All rights reserved.